PENGARUH STRATEGI SEGMENTING, TARGETING DAN POSITIONING TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG DI KELURAHAN PAGAR DEWA KOTA BENGKULU - Putra, Gustiawan; Sismanto, Adi (Yayasan Insani Mandiri Santani, 2021)
This study aims to determine the effect of Segmenting (X1), Targeting (X2), and Positioning (X3) strategies on Purchasing Decisions (Y) of Samsung Mobile Phones in Pagar Dewa Village, Bengkulu city. The formulation of problem in this study whether there was an effect of Segmenting (X1), Targeting (X2), and Positioning (X3) on Purchasing Decisions (Y). This research used quantitative methods. The object of this research were users and consumers of Samsung mobile phones in Pagar Dewa Village, Bengkulu city with the sampling method by using purposive sampling technique. The number of respondents in this study were 85 respondents. Data collection techniques used observations and questionnaires. Data analysis techniques were further analyzed through classical assumption test, multiple linear regression, correlation coefficient and determination (R2), and hypothesis test. The results of multiple linear regression analysis with SPSS 24; regression equation obtained Y= 1.668 + 0.403 (X1) + 0.376 (X2) + 0.095 (X3). This means that there was a positive influence between Segmenting (X1), Targeting (X2), and Positioning (X3) on Purchasing Decisions (Y). The coefficient of determination (R2) was 0.714, which indicated that Segmenting (X1), Targeting (X2), and Positioning (X3) affect the Purchase Decision (Y) by 71.4%, while its remaining 28.6% was influenced by other variables, not in this study. The results of t_test on Segmenting variable (X1) showed thit> ttab (6,836> 1,664) and its value sig Î± = 0,000 <0.050), which showed significant influence between three as shown from its thit>ttab (4.705 >1.664). The significant value Î± = 0.000< 0.050), which showed its significant influence of three variablse as shown from thit> ttab (2.047> 1,664) and value (sig Î± = 0.044 < 0.050) on Purchasing Decisions (Y). The results of the F_test showed that Fhit> Ftab (67,361> 2,717) and (sig Î± = 0.000<0.050), this simultaneously the Segmenting (X1), Targeting (X2), and Positioning (X3) variables have a significant effect on the decision. Purchase (Y).Keywords: Segmenting, Targeting, Positioning, Purchasing Decision